The Relevance of Depressive Symptoms and Social Support to Disability in Women with Multiple Sclerosis or Fibromyalgia - Phillips, Lorraine J. (2010)
Multiple sclerosis (MS) and fibromyalgia syndrome (FM) may spur substantial disability for those affected. Using structural equation modeling (SEM), this secondary analysis examined predictors of disability in women with MS (N=118) and FMS (N=197) recruited for separate wellness studies. Greater functional limitations, lower economic adequacy, less social support, and higher depressive symptoms predicted greater disability in both groups. The final multi-group model demonstrated good fit χ(2)(111, N=315)=135.92, CFI=.99, RMSEA=.03) and identified similarities and differences across groups.